Caracterizaï¿½ï¿½o molecular de Cryptosporidium spp. em criaï¿½ï¿½es comerciais brasileiras de coelhos - Heker, M. M. [UNESP]; Nakamura, A. A. [UNESP]; Meireles, M. V. [UNESP] (FapUNIFESP (SciELO), 2016)
Cryptosporidiosis is an important zoonotic disease that can be transmitted via water, food and contact with infected animals and people. Furthermore, clinical and subclinical disease occur in many animal species, including the domestic rabbit. The objective of this study was to determine the occurrence of Cryptosporidium spp., perform its molecular classification and correlate the presence of the parasite to the different animal categories in Brazilian rabbits farms. A total of 514 fecal samples from 21 rabbits farms located in the states of Minas Gerais, Mato Grosso do Sul, Pernambuco, Paranï¿½, Rio de Janeiro, Rio Grande do Sul and Sï¿½o Paulo were collected and stored in 5% potassium dichromate. Fecal samples were purified by centrifugal-flotation in Sheather solution and screened for Cryptosporidium spp. oocysts using the negative malachite green staining. Aiming the molecular characterization of Cryptosporidium spp., nested PCR targeting the 18S rRNA gene and gp60 gene followed by sequencing of amplified fragments were accomplished in 55 samples. Eight samples were positive for Cryptosporidium spp. by microscopy (1.56%; 8/514) and seven samples were positive by PCR (12.73%; 7/55). Molecular analysis revealed Cryptosporidium cuniculus for the 18S rRNA gene and C. cuniculus subtype VbA21 for the gp60 gene in kits and does.
Molecular characterization of cryptosporidium spp. in Brazilian rabbit farms
Keywords: Brazil; Coccidiosis; Molecular classification; Polymerase chain reaction; Rabbit